(untitled) - Broukal, Milada (Australia, 2005)
Weaving It Together is a four-level series designed to comprehensively integrate reading and writing. It promotes individualized and cooperative learning within the moderate and large-sized classroom.
Keywords: English language; Textbooks for foreign speakers